Antimicrobial resistance and prevalence of Staphylococcus aureus in veterinary sources in south Brazil, 2017–2023 - Rafael Levandowski; Luana Pasqualotto; Milena Zanoello Bertuol; Thabata Alecsandra de Araujo; Bruno Webber Klaser; Fernando Pilotto; Luciana Ruschel dos Santos; Laura Beatriz Rodrigues (Revista de Ciência Veterinária e Saúde Pública, 2025)
Surveillance studies are essential for tracking the emergence and spread of antimicrobial resistance, which can help identify the most effective strategies for international stewardship in containing the spread of resistant infections. This study investigated the prevalence and resistance patterns of Staphylococcus aureus in southern Brazil from 2017 to 2023. A total of 3,435 clinical specimens were collected from veterinary sources and tested for Staphylococcus aureus. Antibiotic susceptibility testing was performed using the disc diffusion method, and a new categorization of antibiotics based on resistance levels was proposed. The results showed that Staphylococcus aureus isolates exhibited high resistance to various commonly prescribed antibiotics, with significant differences among antibiotic classes. Multidrug resistance showed temporal variations, with a peak of 54.29% in 2021. The study suggested that empirical treatment guidelines may need revision, and regional variations in antimicrobial resistance rates should be considered. These results also highlight the dynamic nature of antimicrobial resistance and indicate the need for continuous surveillance and rational use of antibiotics to prevent the dissemination of resistant strains of Staphylococcus aureus from veterinary sources.